Magnetic Nanoparticles to Recover Cellular Organelles and Study the Time Resolved Nanoparticle‐Cell Interactome throughout Uptake. Issue 16 (16th April 2014) - Bertoli, Filippo; Davies, Gemma‐Louise; Monopoli, Marco P.; Moloney, Micheal; Gun'ko, Yurii K.; Salvati, Anna; Dawson, Kenneth A.
<x xml:space="preserve">Abstract</x> Nanoparticles in contact with cells and living organisms generate quite novel interactions at the interface between the nanoparticle surface and the surrounding biological environment. However, a detailed time resolved molecular level description of the evolving interactions as nanoparticles are internalized and trafficked within the cellular environment is still missing and will certainly be required for the emerging arena of nanoparticle‐cell interactions to mature. In this paper promising methodologies to map out the time resolved nanoparticle‐cell interactome for nanoparticle uptake are discussed. Thus silica coated magnetite nanoparticles are presented to cells and their magnetic properties used to isolate, in a time resolved manner, the organelles containing the nanoparticles. Characterization of the recovered fractions shows that different cell compartments are isolated at different times, in agreement with imaging results on nanoparticle intracellular location. Subsequently the internalized nanoparticles can be further isolated from the recovered organelles, allowing the study of the most tightly nanoparticle‐bound biomolecules, analogous to the 'hard corona' that so far has mostly been characterized in extracellular environments. Preliminary data on the recovered nanoparticles suggest that significant portion of the original corona (derived from the serum in which particles are presented to the cells) is preserved as nanoparticles are trafficked through the cells.